Law and society reconsidered - Sarat, Austin (Studies in law, politics, and society, 2007)
This volume of "Studies in Law, Politics, and Society" presents a diverse array of interdisciplinary research. It contains articles by scholars from political science, sociology, and law. These articles examine the legal treatment of 'suspect' populations, the work of legal actors, and the works of various legal devices. Taken together the work published in this volume exemplifies the kind exciting and innovative work now being done by legal scholars from different disciplines. This book contains contributions from law and society scholars from political science, anthropology, sociology, and law and a comprehensive assessment of the state-of-the-field, its past, and its trajectory for the future.